Peculiarities of the Call Flow Service by Small Capacity Exchanges - Rindzevicius, R.; Cenkus, A. (Elektronika ir Elektrotechnika, 2000)
Telephone customers requesting telephone lines in the exchange are examples of calling population. The most commonly assumed call arriving patern is the Poission process, described by Erlang’s loss system.The finite call population service are described by Engset’s loss system. Analytic and simulation models of system are created. Some results of analytic and simulation models are presented.